2020
DOI: 10.1002/jcla.23496
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA XIST binding to let‐7c‐5p contributes to rheumatoid arthritis through its effects on proliferation and differentiation of osteoblasts via regulation of STAT3

Abstract: Rheumatoid arthritis (RA) is a chronic and inflammatory disorder, which can result in joint destruction, deformity, and even disability. 1 However, the etiology and pathogenesis of RA remain unclear, although it has been hypothesized that RA may result from the combined effects of genetic and environmental factors. 2,3 RA is associated with multiple characteristics, including cartilage degradation, bone erosion, and joint instability. 4 Nowadays, RA is reported to affect approximately 1% of the world populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Studies have clarified that lncRNA NEAT1 could bind to miR-129/miR-204 (188), miR-410-3p (189), and miR-23a (190), thereby regulating cell viability, migration, and inflammation in fibroblast−like synoviocytes from RA. Furthermore, the up-regulated lncRNA ZFAS1 (155,191), HIX003209 (156), and XIST (192) and down-regulated lncRNA LINC01197 (193), GAS5 (154), and OIP5-AS1 (194) also sponged miRNAs, thereby participating in cell proliferation, differentiation, apoptosis, and inflammation in synovial tissue of RA via ZFAS1/miR-2682-5p/ADAMTS9 axis, ZFAS1/miR-296-5p/MMP-15 axis, HIX003209/miR-6089/TLR4 axis, lncRNA XIST/let-7c-5p/STAT3 axis, LINC01197/miR-150/THBS2 axis, GAS5/miR-128-3p/HDAC4 axis, and OIP5-AS1/miR-448/ PON1, respectively. The details are presented in Table S1.…”
Section: The Crosstalk Of Lncrnas Mirnas and Mrnas In Ramentioning
confidence: 99%
“…Studies have clarified that lncRNA NEAT1 could bind to miR-129/miR-204 (188), miR-410-3p (189), and miR-23a (190), thereby regulating cell viability, migration, and inflammation in fibroblast−like synoviocytes from RA. Furthermore, the up-regulated lncRNA ZFAS1 (155,191), HIX003209 (156), and XIST (192) and down-regulated lncRNA LINC01197 (193), GAS5 (154), and OIP5-AS1 (194) also sponged miRNAs, thereby participating in cell proliferation, differentiation, apoptosis, and inflammation in synovial tissue of RA via ZFAS1/miR-2682-5p/ADAMTS9 axis, ZFAS1/miR-296-5p/MMP-15 axis, HIX003209/miR-6089/TLR4 axis, lncRNA XIST/let-7c-5p/STAT3 axis, LINC01197/miR-150/THBS2 axis, GAS5/miR-128-3p/HDAC4 axis, and OIP5-AS1/miR-448/ PON1, respectively. The details are presented in Table S1.…”
Section: The Crosstalk Of Lncrnas Mirnas and Mrnas In Ramentioning
confidence: 99%
“…The lncRNA XIST affects the proliferation and differentiation of osteoblasts by binding let-7c-5p to regulate signal transducer and activator of transcription 3 ( STAT3 ), thereby promoting the occurrence of RA. 60 Quercetin can inhibit TNF-α-induced inflammatory cytokine production and XIST expression in RA-FLS, and silencing XIST can inhibit the inflammatory response of TNF-α-treated cells through miR-485. 4 The interaction between lncRNA XIST and miR-126-3p regulates the NF-κB signaling pathway in RA-FLS; downregulation of XIST can inhibit the proliferation of FLS by increasing the expression of miR-126-3p/NF-κB, thereby inhibiting the occurrence and development of RA.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In patients with rheumatoid arthritis, high expression level of let-7c led to decreased levels of TNF-α, IL-2, and IL-6, suggesting suppression of the inflammatory response. 40 Let-7c can also regulate inflammation under oxidative stress in lens epithelial cells by targeting ATG3, which prevents the formation of cataracts. 41 In the present study, we found that let-7c was a key signaling factor for macrophage polarization and inhibition of UFB activation.…”
Section: Discussionmentioning
confidence: 99%